Cross-reactivity of antibodies directed to the gram-negative bacterium Neisseria gonorrhoeae with heat shock protein 60 and ATP-binding protein correlates to reduced mitochondrial activity in HIBCPP choroid plexus papilloma cells - Reuss, Bernhard; Schroten, Horst (Journal of molecular neuroscience, 2015)
Antibacterial antibodies can cause neurologic side-effects by cross-reactivity with cellular antigens. Here we investigated interactions of antibodies to Neisseria gonorrhoeae (α-NG) - maternal infections by which increases the offspring’s risk for later psychosis—with HIBCPP cells, a cell culture model of choroid plexus epithelium. Immunocytochemistry and Western blotting with α-NG, revealed organelle-like intracellular staining in HIBCPP cells, and labelling of several immunoreactive bands in cellular protein. Two-dimensional Western blotting revealed several immunopositive spots, most prominent of which were identified by mass spectrometry as mitochondrially localized proteins heat shock protein 60 (Hsp60) and ATP-binding protein β-subunit (ATPB). Similarly α-NG interacted with commercial samples of these proteins as revealed by Western blotting. Three alternative methods (JC-1, Janus green and MTT staining) revealed α-NG to cause in HIBCPP cells a significant decrease in mitochondrial activity, which could be reverted by neuroleptic drugs. Immunoreactivity of α-NG with choroid plexus epithelium in human post mortem samples suggests in vivo relevance of these findings. Finally, distinctly different staining patterns of antibodies against Neisseria meningitidis (α-NM), confirmed antibody specificity. To our knowledge this is the first report that α-NG cross-reactivity with Hsp60 and ATPB impairs mitochondrial activity in choroid plexus epithelial cells, pathogenetic relevance of which needs further clarification.